Coronary Virtual Intravascular Endoscopy - Sun, Zhonghua (Springer-Verlag London Ltd, 2014)
Virtual endoscopy is a 3D visualisation tool which provides unique intraluminal information of hollow organs and anatomical structures by utilising volumetric dataset. Coronary virtual intravascular endoscopy (VIE) represents a specific application of virtual endoscopy in the diagnostic evaluation of coronary anatomy, coronary artery disease including plaque assessment, coronary stents and coronary artery bypass grafting. This chapter presents information about coronary VIE generation, intraluminal appearances of normal coronary artery, coronary plaques with regard to different types of plaques, coronary stents in terms of normal patent stents and in-stent restenosis, and coronary artery bypass grafting.